Analisis Penggunaan Alat Flow Meter Pada Sistem Pencampuran Air dan Kapur di PT Krakatau Tirta Industri Cilegon - Yogi Ramadani; Suhendar Suhendar (Politeknik Kampar, 2024)
Analysis Of The Use Of Flow Meter Equipment In Mixing Water And Lime At Pt Krakatau Tirta Industri. Flow meters are vital instruments in measuring and controlling fluid flow at PT Krakatau Tirta Industri, especially in mixing water and lime which affects product quality. This study analyses the effectiveness of electromagnetic flow meters in improving efficiency and maintaining mix ratio. Data were collected through direct observation and tool performance evaluation. The results show that electromagnetic flow meters provide high accuracy, reduce measurement errors, and improve production efficiency. Recommendations are given for periodic maintenance and calibration to maintain optimal performance.